Formation of graphic competence of junior professionals through distance learning technologies - Воронцова, Ірина; Лук’янець, Володимир; Шумська, Любов (Educational Dimension, 2015)
Vorontsova I. V., Lukyanets V. D., Shumskaya L. P. Formation of graphic competence of junior professionals through distance learning technologies. The article deals with the theoretical and methodological foundations of distance learning as one of the important factors of pedagogical cooperation of the teacher and the student. The article analyzes the possibilities of a distance course on technical drawing in the forming of graphical competence of junior specialists.